Efficacy of Sugarcane Bagasse and Rice Husk Adsorbent for treatment of Heavy metals from petroleum refinery effluent - Waziri, S. A.; Mustapha, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Heavy metals are being extremely released into the environment due to poor was management resulting from industrialization and urbanization. Discharging wastewater contaminated with heavy metals poses a significant risk to human health and the surrounding ecosystem. Heavy metals are characterized by their non-biodegradable nature and potential carcinogenic properties. Activated carbons (ACs), which are carbon-based nano-porous adsorbents, are widely utilized in the removal of heavy metals because of their extensive surface area. In this study, active carbon materials were prepared using rice husk and sugarcane precursor by applying physical-chemical activation methods. To examine the Sequestering of heavy metals (cadmium, chromium, copper, lead, nickel, and zinc) in a refinery effluent, a batch adsorption technique was adopted, and the process parameter were investigated at different temperatures and impregnation ratio. Scanning Electron Microscope (SEM) and Fourier-Transform Infrared Spectroscopy (FTIR) were used to determine the surface morphology and functional group while X-Ray Diffraction analysis (XRD) was used for the study of the crystallographic property of the activated carbon adsorbent. Both Rice Husk and Bagasse showed promising capacity for multiple adsorption of heavy metals. Freundlich and Langmuir's models were applied to study the sorption behavior. Although, process parameters play a vital role in the activation of the adsorbent, rice husk, and sugar bagasse have a strong potential for heavy metal adsorption. The hierarchy of performance effectiveness of rice husk was Cr>Pb>Cu>Cd>Zn>Ni according to the Langmuir model with Chromium (Cr) having the highest performance with a coefficient of correlation R2 of 0.9512 and the least Nickel (Ni) having R2 of 0.6156. While Sugarcane bagasse fitted well to the Freundlich model with the efficacy of removal in the order Pb>Cu>Cd>Ni>Cr>Zn with Lead (Pb) having the highest efficacy of removal with R2 of 0.957 and the least was Zinc (Zn) with R2 of 0.211 respectively.